THE DIFFERENCE IN QUALITY OF LIFE AMONG THE ELDERLY LIVING IN COMMUNITIES AND NURSING HOME RUMOH SEUJAHTERA GEUNASEH SAYANG IN BANDA ACEH - Arlianti, Nopa; Wardiati, Wardiati; Lutfia, Humairah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: The increase in the number of elderly in the world causes a variety of problems, one of which is the low quality of life of the elderly which is influenced by several factors such as housing factors, physical and psychological conditions, and social and cultural factors. This study aims to find out the difference in the quality of life of elderly people living in communities and living in nursing home. Methods: This study uses cross-sectional design with a population consists of 2 groups, namely the elderly living in the communities and nursing home. The elderly sample in the nursing home is determined by the total method of the population. While sampling elderly samples in the communities using purposive sampling method with a sample ratio 1:1. Data collection was conducted by interview using the WHOQOL-Bref questionnaire. Univariate and bivariate analysis was used to analyze the data and t-test independent was utilized to examine the difference in the quality of life among studied groups. Result: The results showed that the average age of the elderly living in the nursing home was younger, and majority of respondents did not graduate from elementary school. Univariate analysis shows that elderly people living in the nursing home have a better quality of life compared to the elderly living in the community. Bivariate analysis showed that there is a significant differences between the quality of life of eldery people living in nursing home and in the community, both from the physical domain of the eldery (p-value: 0.0003), the psychological domain (p-value: 0.0349), the social domain (p-value: 0.0001), and the environmental domain (p-value: 0.0001). Recommandation: Efforts to improve the elderly’s quality of life are required to be done by families, communities, and governments. Thus, the elderly can go through their old age in a healthy, safe and comfortable manner.